Sorption Isotherm Phenomena in Cured Oriental Tobacco I. Water Activity Behavior and Hysteresis - Amin, Aumeed Noori M. (Sulaimani Journal for Pure and Applied Sciences, 1997)
valuable information can be obtained from the examination of moisture content of tobacco leaves in relation to environmental conditions, especially during the time course of handling. Moisture sorption isotherms of locally grown tobaccos were examined. Tobacco leaves of cultivars behaved differently in term of water activity. Moisture sorption isotherms of midrib were higher than those of laminal. Temperature dependence of sorption isotherms were apparent. Hysteresis phenomena were distinct. Leaves were different in their hysteresis.